PWE-075 Lack of association between the PSCA rs2294008 polymorphism, or PSCA expression, and colorectal neoplasia. (28th May 2012) - Smith, C; Lochhead, P; Basavaraju, U; Hold, G; Fyfe, N; Murray, G; El-Omar, E
Abstract : Introduction: Prostate stem cell antigen (PSCA) has been implicated in the pathogenesis of several solid tumours, either due to changes in protein expression, or through association with the rs2294008 (C>T) polymorphism in the PSCA gene. From in vitro data, this polymorphism appears to be functional, and the risk allele (T) has been shown to be associated with gastric cancer risk in Asians and white individuals. Our study aimed to test for associations between the rs2294008 polymorphism, or PSCA protein expression, and risk of adenomatous polyps and colorectal cancer. Methods: Between 2008 and 2010, we recruited individuals who had tested positively for faecal occult blood, and had undergone colonoscopic screening. Genomic DNA samples were available from 388 subjects with histologically-proven colorectal neoplasia and 493 subjects with no evidence of neoplasia. Genotyping for the rs2294008 polymorphism was performed using a pre-designed TaqMan® assay and the ABI 7900HT Fast Sequence Detection System. Immunohistochemical (IHC) staining for the PSCA protein was performed using normal and neoplastic tissues covering all stages of the adenoma-carcinoma sequence. The tissue set included adenomatous polyps displaying low-grade (n=10), and high-grade (n=10) epithelial dysplasia, and adenomatous polyps harbouring invasive carcinoma (n=10). Normal adjacent mucosa was assessed in the polyp sections in addition to separate normal mucosal sections (n=4). Positive staining of colonic crypt neuroendocrine cells served as an internal positive control. Results: There was no association between the rs2294008 SNP and risk of colorectal neoplasia in either dominant (OR 0.97; 95% CI 0.73 to 1.28) or recessive (OR 0.88; 95% CI 0.61 to 1.27) genotype models. IHC analysis of colonic tissue samples indicated no alteration in the topographic distribution or intensity of PSCA staining between normal mucosa, adenomatous mucosa with low or high grade epithelial dysplasia, and invasive carcinoma. Conclusion: Our results suggest that PSCA does not play an important role in the initiation or progression of colorectal carcinogenesis. Given that PSCA has been implicated in a variety of other solid tumours, continued efforts should be made to elucidate the normal and pathological cellular functions of PSCA. Competing interests: None declared.